The Phase Effect of Exercise I Heart Rehabilitation on Self-Care and Patient Life Quality with Coronary Heart Disease over PGI Cikini Hospital 2017 - Yannerith Chintya; Risma Yuniarlina; Wilhelmus Hary Susilo (Journal of Multidisciplinary Academic, 2019)
The Phase I Heart Rehabilitation Exercise it’s one of an efforts to achieve functional level to allows patients on conduct their initial activities such as in preparation for carrying out daily activities at home also for prevention of adverse effects 'deconditions' due to prolonged bed rest. This study, we conducted coronary heart disease which is generally given to a total bed rest during heart rehabilitation training phase I and exercise. Thus, this study aims to determine the cardiac effect in rehabilitation training phase I on self-care and patients life quality with coronary heart disease, using quasi experimental method with pretest-posttest control group. Here, we take 81 respondents of coronary heart disease in a stable state condition. The results showed that the first phase of cardiac rehabilitation exercises is significantly affected over self-care (p = 0,000) while the quality of life (p = 0,000) is increased with odds ratio three times and improved quality of life with odds ratio four times. The iIntervention group compared with control group. Based our study, the Phase I heart rehabilitation exercises is recommended for stable coronary heart disease.